PPE18 and PepA Variations in Mycobacterium tuberculosis Clinical Isolates from Makassar, Indonesia: Challenges for Immune Recognition and Vaccine Development - Stephanie Cynthia Theorupun; Muhammad Nasrum Massi; Astutiati Nurhasanah; Fadhilah Syamsuri; Mochammad Hatta; Yoeke Dewi Rasita; Najdah Hidayah; Nihayatul Karimah; Doddy Irawan Setyo Utomo (International Journal of Mycobacteriology, 2025)
Background: The M72/AS01E tuberculosis vaccine candidate, currently on trial in Indonesia, includes PPE18 (Rv1196) and PepA (Rv0125) as key antigens. Genetic variation in these proteins may affect immune recognition and vaccine efficacy. This study aims to analyse the genetic diversity of Rv1196 and Rv0125 in Mycobacterium tuberculosis clinical isolates from Indonesia and assess the structural and immunological implications using in silico methods. Methods: Rv1196 and Rv0125 genes from clinical isolates were sequenced and analysed for polymorphisms. PPE18 variants were modelled using I-TASSER (Iterative Threading ASSEmbly Refinement), and structural stability and HLA (Human Leukocyte Antigen) binding predictions (HLA-I and HLA-II) were performed using IEDB (Immune Epitope Database) tools. Molecular docking with TLR2 (Toll-like Receptor 2) was conducted to evaluate receptor interactions. Results: A novel non-synonymous mutation (T22G, Ser8Ala) was identified in Rv0125, which was otherwise conserved. Rv1196 showed high variability with 58 polymorphic sites, including 38 non-synonymous mutations, a frequent Arg287Gln substitution, and a ΔThr163-Ala164 deletion. Structural modelling indicated preserved PPE18 fold but altered epitope binding in an allele-specific manner. Docking showed stronger TLR2 interactions for variants 6S31 and 6S32, suggesting enhanced IL-10 induction and a Th2-skewed immune response. Conclusions: PPE18 genetic variation may influence immune recognition and the effectiveness of M72/AS01E. Ongoing antigenic surveillance in endemic areas is essential to guide vaccine design and diagnostics.